Molecular identification of staphylococcus epidermidis and corynebacterium species in nasal isolates among medical laboratory technology students in UiTM Puncak Alam / Nur Zarith Fatihah Johari - Johari, Nur Zarith Fatihah (2016)
Staphylococcus epidermidis and Corynebacterium species are opportunistic human pathogens and they are human nasal flora with the capability to survive in hospital environments. This two types of organism colonize a sizeable proportion of the human population and has become the most important cause of nosocomial infections in recent years. Students of Medical Laboratory Technology (MLT) often exposed to the hospital environments, hence increasing the chances of carrying and spreading these organisms to the community and patients. Thus, this research aim to determine the prevalence of Staphylococcus epidermidis and Corynebacterium spp. from nasal isolates of MLT students in UiTM Puncak Alam. In this research, 144 students are involved which consists of 70 and 74 pre-clinical and clinical students respectively. During sampling, a self-administered questionnaire was given and nasal swab were collected. Several identification test are performed to identify S. epidermidis and Corynebacterium spp. from the sample. Further reconfirmation was performed by real time polymerase chain reaction (qPCR), which targeting SE1 and PAC (tox) gene respectively, and the data obtained are analyse with categorical analysis (i.e. Chi-square and Fisher’s exact tests). 53 (36.8%) S. epidermidis were isolated in which 29 (41.4%) were from clinical while the remaining 24 (32.5%) were from pre-clinical students. There was no significant relationship between S. epidermidis and Corynebacterium spp. nasal isolates and clinical attachment status (p>0.05). There was no statistical relation with gender (p =0.895) and race (p=0.669). Besides, the relationship between S. epidermidis and Corynebacterium spp. nasal carriage with gender, race, medical history and hygienic factors in pre-clinical and clinical groups were also not significant. There was no Corynebacterium spp. isolated in this study.